The relevance of comparative fiqh in contemporary Islamic jurisprudence - Muhammad Hafiz, Muhammad Danial Haikal; Abd Halim, Muhammad Silahuddin; Narizam, Ahmad Tawfiq; Zamri, Muhammad Hanis Khairul; Shahabuddin, Muhammad Syakib Najmii (2025)
This assignment examines the role of fiqh muqaran in ensuring the effectiveness and acceptability of Islamic law in the contemporary context. Through a comparative fiqh approach that highlights the elasticity and accountability of evidence, this study emphasizes the importance of critical analysis of various school opinions in order to produce answers that are appropriate to modern challenges such as bioethics, finance, and medical technology. Despite its considerable benefits, the implementation of fiqh muqaran faces methodological challenges, institutional constraints, and a lack of cross-school training that hinder its widespread use in current Islamic legal decision-making institutions. This study also highlights the need to improve education and training in this field so that it can contribute constructively to maintaining the relevance of sharia law in the dynamic modern world.